Krisis Bosnia-Herzegovina 1908: peranan dan reaksi kuasa-kuasa besar. - Azlizan Mat Enh, (Universiti Kebangsaan Malaysia, 2010)
The crisis in Bosnia-Herzegovina started in the year 1908. The crisis was caused by the Austria-Hungary’s action, which declared Bosnia-Herzegovina as part of its permanent empire. The declaration was considered illegal because it was made without the consent of the European super powers who had signed the Berlin Treaty 1878. Bosnia- Herzegovina was Uthmaniah’s colony, but due to the rebellion in 1875-1878, Austria-Hungary was given the mandate by the super powers, through the Berlin Treaty of 1878, to temporarily manage Bosnia-Herzegovina, that is until peace can be restored in the country. The super powers had different responses toward Austria-Hungary’s action. Russia and Turkey were strictly against the Austria-Hungary decision to control Bosnia-Herzegovina. While other super powers, namely Britain, Germany, French and Italy were of the opinion that the Bosnia-Herzegovina crisis should be immediately settled through negotiation. If the suggestion were not abide, the crisis would invite war between Russia, Austria-Hungary and Turkey government who was still a legal owner of Bosnia-Herzegovina. As a result, the war will drag all the Super Powers to engage in the same detrimental war. The issue that will be discussed here is the Super Powers’ reactions toward Austria Hungary’s decision and how they worked out to Bosnia crisis 1908 to avoid war in Europe. Further, this essay touched the effects of the Austria-Hungary’s action in political scenario in Balkan.